Choroidal melanoma metastatizing to the biliary system: A diagnostic dilemma - Agarwal Samir; Bhattacharya Indranil; Patil Yoganand; Amrapurkar Anjali (Indian Journal of Medical and Paediatric Oncology)
Metastatic melanoma to the gall bladder is extremely rare and is associated with a very poor prognosis. We report a case of choroidal melanoma metastatizing to the hepatobiliary system, with an unusual presentation. Our patient presenting with obstructive jaundice was misdiagnosed as having carcinoma of the gall-bladder, but the diagnosis of metastatic melanoma to the gallbladder was confirmed by ultrasonography guided fine needle aspiration cytology (USG-FNAC). On reviewing the past history, the patient had a history of enucleation for choroidal melanoma. Even though the liver ′is′ a common site for metastasis of choroid melanoma, the patient presenting with a suspected gall bladder mass ′is′ a rare presentation. Hence, gastrointestinal symptoms and a history of melanoma should be investigated for the presence of gastrointestinal or liver metastases, even if the original primary malignancy was diagnosed years before the patient′s presentation.